2011
DOI: 10.2147/ccide.s24064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of myrrh on intra-oral mucosal wounds compared with tetracycline- and chlorhexidine-based mouthwashes

Abstract: Aim:To evaluate the effect of myrrh compared with chlorhexidine gluconate-and tetracyclinecontaining mouthwashes on wound healing over time in an animal model. Methods: A unilateral incision on the right buccal mucosa was made, and the wound was irrigated with myrrh-, chlorhexidine gluconate-, or tetracycline-based mouthwashes at various time intervals. Clinical and histological examination was performed for all the groups. Results: It was found that the myrrh suspension promotes healing and repair of damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…Our findings are consistent with previous reports that indicated the wound care efficacy ( Al-Harbi et al, 1994 , Dolara et al, 1996 , Nomicos, E.Y.H., 2007 ) and anti-inflammatory activity ( Duwiejua et al, 1993 , Lata et al, 1991 , Malhotra et al, 1977 , Tariq et al, 1985 ) of Commiphora molmol . A similar animal model study by Al-Mobeeriek (2011) reported similar clinical results. They used several mouthwash types to compare with myrrh mouthwash and saline mouthwash, which was used by the control group .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings are consistent with previous reports that indicated the wound care efficacy ( Al-Harbi et al, 1994 , Dolara et al, 1996 , Nomicos, E.Y.H., 2007 ) and anti-inflammatory activity ( Duwiejua et al, 1993 , Lata et al, 1991 , Malhotra et al, 1977 , Tariq et al, 1985 ) of Commiphora molmol . A similar animal model study by Al-Mobeeriek (2011) reported similar clinical results. They used several mouthwash types to compare with myrrh mouthwash and saline mouthwash, which was used by the control group .…”
Section: Discussionsupporting
confidence: 63%
“…There are also reports of myrrh being used as a gingival anti-inflammatory toothpaste and mouthwash ( Bradley, 2006 , Saeedi et al, 2003 ). An animal model study reported that application of a diluted suspension of myrrh as a mouthwash stimulated wound healing in injured oral tissue ( Al-Mobeeriek, 2011 ). However, the study suggested possible adverse reaction of the oral tissue to myrrh related to a higher dose, longer time of application, or as part of a reaction to myrrh constituents, regardless of the dose ( Al-Mobeeriek, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Myrrh has been widely used as a wound‐healing commercial product. It has been shown to promote healing and repair of damaged tissue in an animal model . The wound‐healing properties of myrrh may be explained by its ability to induce maturation, differentiation, and activation of WBCs .…”
Section: Discussionmentioning
confidence: 99%
“…Myrrh may have an antiglycemic and antioxidant effect on animals [ 35 ]. It may also be used locally with or without honey for the treatment of wounds even in diabetic patients but for short periods (less than two weeks) and low concentration as it seemed to have harmful adverse events if used in high concentrations or long periods [ 36 , 37 ].…”
Section: The Most Used Tandcm Therapies In Saudi Arabiamentioning
confidence: 99%